Política de assistência estudantil na Universidade Federal da Paraíba : percepções dos discentes assistidos pelo restaurante universitário do campus IV-Rio Tinto - Nascimento, Karina Araújo do (2024)
Given the expansion of higher education in Brazil and the inclusion of historically marginalized segments, it has become necessary to provide support, through public policies, for students in situations of socio-economic vulnerability enrolled in Federal Higher Education Institutions, with a view to improving their conditions of permanence and performance. In this context, this research aims to analyze the National Student Assistance Program at the Universidade Federal da Paraíba (UFPB) focusing on student perceptions of the University Restaurant at Campus Rio Tinto. The investigation was based on the qualitative method and used documentary analysis procedures (Gil, 2008), as well as data collection through questionnaires sent to assisted students. To analyze the data was used Bardin's content analysis (Bardin, 2016). As a final product, based on the indications obtained through the collection, improvements were proposed to the internal policy of the Pro-Rectory for Student Assistance and Promotion.The research revealed that the majority of students give a positive assessment of the RU's assistance, recognizing its capacity to improve their living conditions, even if they also point out suggestions for possible improvements.